2007
DOI: 10.1073/pnas.0610185103
|View full text |Cite
|
Sign up to set email alerts
|

Distortion product otoacoustic emissions measured as vibration on the eardrum of human subjects

Abstract: It has previously not been possible to measure eardrum vibration of human subjects in the region of auditory threshold. It is proposed that such measurements should provide information about the status of the mechanical amplifier in the cochlea. It is this amplifier that is responsible for our extraordinary hearing sensitivity. Here, we present results from a laser Doppler vibrometer that we designed to noninvasively probe cochlear mechanics near auditory threshold. This device enables picometer-sized vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 44 publications
4
37
1
Order By: Relevance
“…Recordable human eardrum displacements causing the 2f 1 -f 2 DPOAE were ~5.6pm when the two tones applied were 65dB SPL and f 1 =4.6kHz and f 2 =5.5kHz. This DPOAE displacement magnitude is consistent with that expected from DPOAE vibration measured at the DPOAE place on the basilar membrane of laboratory animals (Dalhoff et al, 2007). Our results place moth ears above other animals concerning the relative level of DPLDV.…”
Section: Mechanical Distortion-products At the Moth Ear: Vibration Ansupporting
confidence: 79%
See 1 more Smart Citation
“…Recordable human eardrum displacements causing the 2f 1 -f 2 DPOAE were ~5.6pm when the two tones applied were 65dB SPL and f 1 =4.6kHz and f 2 =5.5kHz. This DPOAE displacement magnitude is consistent with that expected from DPOAE vibration measured at the DPOAE place on the basilar membrane of laboratory animals (Dalhoff et al, 2007). Our results place moth ears above other animals concerning the relative level of DPLDV.…”
Section: Mechanical Distortion-products At the Moth Ear: Vibration Ansupporting
confidence: 79%
“…We have shown both in this study (see Figs5,7). In humans and other vertebrates, experiments with LDV techniques found that vibrations inducing DPOAE could be measured on the eardrum (Dalhoff et al, 2007). Recordable human eardrum displacements causing the 2f 1 -f 2 DPOAE were ~5.6pm when the two tones applied were 65dB SPL and f 1 =4.6kHz and f 2 =5.5kHz.…”
Section: Mechanical Distortion-products At the Moth Ear: Vibration Anmentioning
confidence: 96%
“…The auditory threshold thus responds from sub-angstrom oscicular motion. 159,160 This finding has been widely corroborated by Wada et al 161,162 using better-quality tympanometry equipment with low probe tone frequency (time-average speckle pattern interferometry) and finite element analysis at different frequencies and pressures in human and other species' hearing systems. According to Eckerdal 150 , the range of movement of these ligaments depends on the fibrous connection on the walls of the petrotympanic fissure, thereby corroborating Coleman's findings 138 .…”
Section: First Bone Common Passages Explorationsupporting
confidence: 61%
“…The LDV recordings did not show any vibration at the expected frequencies on any point on the membrane. In contrast, for human and other vertebrates, experiments with LDV techniques found that the DPOAE-induced vibration could be measured on the eardrum (Dalhoff et al, 2007). Recordable human eardrum displacements due to the 2f1-f2 DPOAE were 1.3 and 5.6pm when the two tones applied were 25 and 65dB SPL for f1 and f2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recordable human eardrum displacements due to the 2f1-f2 DPOAE were 1.3 and 5.6pm when the two tones applied were 25 and 65dB SPL for f1 and f2, respectively. It should also be noted that other tested vertebrate hearing organs, in guinea pigs, produced even larger displacements of the basilar membrane (Dalhoff et al, 2007).…”
Section: Discussionmentioning
confidence: 99%